Numerical Investigation for Selection the Optimal Flexural Strengthening Strategy of Reinforced Concrete Beams - Abdulkhudhur , Raad; Hardan Dawood , Murtadha; Al-Quraishi, Hussein (Civil Engineering Journal, 2025)
Reinforced concrete is the most widespread material that is used in structural applications. In structural systems, concrete beams can become damaged due to aging and increased design loads. Furthermore, for architectural purposes, specific dimensions may be imposed on concrete beams. For these reasons, it always needed to strengthen these beams. In this study, a numerical study was conducted to simulate the strengthening and improving of the flexural strength of reinforced concrete beams using three techniques: carbon fiber (CFRP sheets), steel plate, and external bars. The numerical analysis was verified with previous experimental studies. For the parametric study, the thickness, number of layers, and tensile strength were adopted for the CFRP strengthening technique. For the steel plates, the effect of changing the thickness and number of layers and yield stress was studied. Finally, for the additional external bars, different ratios of longitudinal reinforcement were investigated. After conducting numerical analysis of the studied models, the results showed a clear increase in the ultimate load and stiffness of the beams when strengthened with carbon fiber and steel plate, especially when increasing the tensile strength and yield strength, which was the most influential parameter, compared to a very limited effect of the number of layers due to the separation between the layers, especially for CFRP. However, both strategies showed brittle failure without clear ductility. Using additional external bars or increasing the ratio of longitudinal reinforcement was the most influential strengthening strategy in terms of increasing the beams’ capacity for bending and ductility.